Application of Problem Based Learning to Increase Creativity and Achievement Learning Outcomes of Students at State Vocational High School 3 Yogyakarta - Eko Mulyadi (Cakrawala Jurnal Ilmiah Bidang Sains, 2022)
This Classroom Action Research aims to increase the creativity and achievement of Physics learning outcomes of students. This study was carried out in three cycles, each cycle consisting of 3 meetings. Each cycle includes four steps, namely planning, action, observation, and reflection—the results of achievement in learning. Creativity improvement in cycle 1 was 78.00, in cycle 2 was 83.70, and in cycle 3 was 82.34 there was an increase of 5.7. The achievement on average pre-cycle 32.00, cycle 1 on average 59.68, cycle 2 on average 60.71, cycle 3 on average 71.93, This study is 3 cycles because in cycle 3, student creativity has reached 80, and student absorptive capacity reaches 70. The PBL models need to be applied because of an increase in both creativity and learning outcomes